Cushing's disease presenting with psychosis. Issue 4 (23rd July 2021) - Mubarak Mohamed, Ahmed Saeed; Iqbal, Ahmed; Prasad, Suveera; Hoggard, Nigel; Blackburn, Daniel
Abstract : Cushing's disease is a rare endocrine condition in which a pituitary corticotroph adenoma drives excess adrenal cortisol production, and is one cause of endogenous Cushing's syndrome. We present a young woman with 3 weeks of headaches and cognitive disturbance who subsequently developed florid psychosis requiring multiple admissions under neurology and psychiatry. Her clinical stigmata of hypercortisolism and biochemical abnormalities prompted an MR scan of the pituitary, which confirmed a pituitary microadenoma. Treatment with metyrapone and subsequent surgery led to complete recovery within 2 months. Cushing's disease commonly causes neuropsychiatric symptoms and can present with psychosis. Diagnosing Cushing's disease can be challenging, but with early diagnosis and treatment it has an excellent prognosis.